Interaction of Russia and OSCE in the Field of Electoral Legislation and Elections - E. V. Makhora (Проблемы постсоветского пространства)
In article the author investigates history and problems of interaction of Russia and OSCE in the field of electoral laws; analyzes documents of the CEC concerning an order of activity of foreign (international) observers, the documents of the OSCE/ODIHR devoted to elections to the State Duma in 2011 and in 2016.